PENEGAKAN HUKUM LALU LINTAS MELALUI E-TILANG DALAM MENINGKATKAN KESADARAN HUKUM BERLALU LINTAS DI KOTA LUBUK LINGGAU - Serlika Aprita; Meirina Nurlani (CV. Cendikiawan Muda Sriwijaya, 2024)
Abstract The implementation of electronic tickets can have a positive influence in the midst of the low legal awareness of the people of Lubuk Linggau City in traffic. E-ticketing speeds up the process of taking action against traffic violations. With technology, violations can be detected automatically through CCTV cameras. The National Police of the Republic of Indonesia implements a traffic order enforcement strategy known as E-TLE, which is an electronic system to monitor and implement traffic regulations in electronic form that utilizes supporting resources such as CCTV. CCTV footage is used as evidence, this system uses video cameras to display and record images at a specific time and location where the device is located, which implies a closed signal. Keywords: Traffic, E-Ticket, Electronic Traffic Law Enforcement, Legal Awareness